Study of the structural and Electrical properties of cadmium selenide Doped With zinc in Different proprtions - Imad Kadhim Khudhair (University of Thi-Qar Journal of Science, 2025)
Three samples of pure CdSe doped with zinc (4% and 8%) were prepared by the slow cooling method at 325°C and pressed into discs. The structural properties of the prepared samples were studied using XRD. It was found that the structure was cubic and polycrystalline, as the crystallization phase did not change as a result of doping with zinc. Using a Senko fluorescence spectrometer, the fluorescence spectrum of the prepared samples was studied, and it was observed that the intensity of fluorescence increases with zinc doping ratio due to the appearance of two peaks at 631.8nm and 704.9nm. By studying the electrical properties (I-V) of the prepared samples, it was observed that there is an improvement in the electrical conductivity of the compound (CdSe) after doping it with zinc, and from calculating the activation energy (Ea) of the samples, it was found that it decreases with increasing zinc doping ratio in order to form impurity levels above the energy gap.